A Planning Law Perspective On Abandoned Housing Projects In Malaysia - Md. Dahlan, Nuarrual Hilal; Mohamed Nafees, Seeni Mohamed; Ahmad, Muhamad Hassan (UNISSULA PRESS, 2019)
Housing is a burgeoning industry in Malaysia. Initially, housing accommodation was provided by the Malaysian Federal Government in the early days of its independence. Later, the private sector was invited by the government to participate in providing housing accommodation to meet the public upsurges in demand for housing. To govern the housing industry spearheaded by the private sector, the Malaysian Government introduced laws. One of the laws is the Town and Country Planning Act 1976 (Act 172) (‘TPCA’). Despite there are many housing policies and legal means to ensure housing success, there are still issues plaguing housing industry in Malaysia. For instance, one of the significant problems is the issue of abandoned housing projects. This issue has been existed since the 1970s. Nonetheless, hitherto this issue has not been adequately addressed and resolved. Many purchasers have become victims in abandoned housing projects, suffered irreparable damage, and excessive losses. The objective of this chapter is to discuss the issues arising from the planning law that govern housing development projects in Malaysia. The purpose of the planning law is to ensure the housing development projects are successful and sustainable for human lives and harmonious with the environment. This writing is pertinent, particularly in the event of abandonment of housing development projects, which hitherto have not been fully resolved in Malaysia. By identifying the issues, the authors will suggest some proposal to overcome the problems and provide better protection to house purchasers and other stakeholders. This chapter analyses planning legal issues about two (2) abandoned housing projects in Malaysia. The investigation is done by applying qualitative case study and legal research methodologies over these two abandoned housing projects. These two housing projects are: 1) Taman Harmoni, Lot 82, Mukim of Cheras, District of Hulu Langat, at the State of Selangor, Malaysia (‘Taman Harmoni’); and, 2) Taman Lingkaran Nur, KM 21, Jalan Cheras-Kajang, Selangor at P.T. 6443, H.S(D) 16848, Mukim of Cheras, District of Hulu Langat, also at the State of Selangor, Malaysia (‘Taman Lingkaran Nur’).